1977
DOI: 10.1677/joe.0.0720361
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oxygen Tension on Somatomedin Activity in Vitro

Abstract: Somatomedins are the intermediaries through which growth hormone acts on the epiphyseal growth plate to effect linear skeletal growth. Rat epiphyseal chondrocytes were isolated and cultured in vitro in the presence of somatomedin. Two sources of somatomedin were used, foetal calf serum and rat liver perfusates. The chondrocytes proliferated and synthesized sulphated glycosaminoglycans when grown in the presence of somatomedin from either source, but were not metabolically active in chemically defined medium al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Hypoxia enhances the ability of chondrocytes to incorporate thymidine in response to IGF-I (Dehnel and Hamblen, 1977). Our laboratory has recently shown that PMA pretreatment allows PA SMC to proliferate in response to hypoxia (Dempsey et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia enhances the ability of chondrocytes to incorporate thymidine in response to IGF-I (Dehnel and Hamblen, 1977). Our laboratory has recently shown that PMA pretreatment allows PA SMC to proliferate in response to hypoxia (Dempsey et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The more rapid proliferation of fibroblasts in hypoxic regions of tissue during wound healing (43) may be reflected in the more rapid growth of these cells at oxygen tensions of 20 to 40 mm Hg in vitro (10,11). Chondrocytes proliferate more rapidly in the relatively avascular core of the developing limb bud (44) and in avascular growing mature cartilage, as well as at lower oxygen tensions in vitro (12). Cardiac enlargement in hypoxic fetuses (45) may result, at least in part, from more rapid proliferation of embryonic myocardial cells at decreased oxygen tensions (13).…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation could be accelerated by hypoxia itself, as has been reported for fibroblasts (10, II), chondrocytes (12), and embryonic myocardial cells (13). We have examined the effects of oxygen tension on proliferation of SMC cultured from the pulmonary arteries of near-term bovine fetuses.…”
mentioning
confidence: 81%
“…Ashton & Francis (1977) and Corvol et al (1978) developed a bioassay for serum somatomedins using rabbit chon¬ drocytes and Dehnel & Hamblen (1977) used rat epiphyseal chondrocytes. Yasumoto et al (1980) reported that the chondrocytes obtained from 13 day old chick embryos could easily be cultured in the floating state, retaining the phenotypic proper¬ ties as chondrocytes.…”
mentioning
confidence: 99%